Combined vitamin C and E deficiency induces motor defects in gulo−/−/SVCT2+/− mice. (May 2013) - Pierce, Marquicia R.; DiAsio, Danielle L.; Rodrigues, Laurisa M.; Harrison, Fiona E.; May, James M.
Abstract : Objectives: Key antioxidants, vitamins C and E, are necessary for normal brain development and neuronal function. In this study, we depleted both of these vitamins in two mouse models to determine if oxidative stress due to combined vitamin C and E dietary deficiency altered their neurological phenotype. The first model lacked both alleles for the Gulonolactone oxidase gene (Gulo −/− ) and therefore was unable synthesize vitamin C. To obtain an additional cellular deficiency of vitamin C, the second model also lacked one allele for the cellular vitamin C transporter gene (Gulo −/− /SVCT2 +/− ). Methods: The experimental treatment was 16 weeks of vitamin E deprivation followed by 3 weeks of vitamin C deprivation. Mice were assessed for motor coordination deficits, vitamin levels, and oxidative stress biomarkers. Results: In the first model, defects in motor performance were more apparent in both vitamin C-deficient groups (VE+VC−, VE−VC−) compared to vitamin C-supplemented groups (VE+VC+, VE−VC+) regardless of vitamin E level. Analysis of brain cortex and liver confirmed decreases of at least 80% for each vitamin in mice on deficient diets. Vitamin E deficiency doubled oxidative stress biomarkers (F2 -isoprostanes and malondialdehyde). In the second model, Gulo −/− /SVCT2 +/− mice on the doubly deficient diets showed deficits in locomotor activity, Rota-rod performance, and other motor tasks, with no concomitant change in anxiety or spatial memory. Discussion: Vitamin E deficiency alone caused a modest oxidative stress in brain that did not affect motor performance. Adding a cellular deficit in vitamin C to dietary deprivation of both vitamins significantly impaired motor performance.